Shrink-wrapped pomegranates stay fresh and nutritive - Sharma, R R; Sagar, V R; Kumar, Kuldeep; Kumar, Jayant; Parmar, Y S (Indian Horticulture, 2019)
Pomegranate has emerged as an important cash crop of India. Now, its area is expanding to even to untapped regions of our country. From production centres, it has to be transported to far flung areas by trucks, rails etc., which sometimes makes it unattractive to consumers and incur heavy post-harvest losses. Although, shelf-life of pomegranate is quite high, still there is a great scope to enhance its availability for a longer period for getting higher price during the lean period. For this, shrink-wrapping technology has been standardized at IARI, New Delhi, by which fruits can be kept in fresh condition for about 2 months without significant loss in juice content and nutritive quality.